2021
DOI: 10.1016/j.ajic.2021.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Clostridioides difficile at an Urban Hospital During Initial COVID Pandemic Wave

Abstract: Background During the first three months of the COVID 19 pandemic, our facility cared for an influx of patients. At the peak, the daily census exceeded 200 patients with COVID 19. Surveillance for healthcare acquired infections (HAIs) continued throughout this time. Despite the acuity of the patients and the frequent use of antibiotics, the rates of Clostridioides difficile lab ID (CDI) events remained relatively stable. We sought to determine the validity of this rate. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Researchers have suggested that this may be due to: resources shortages; influx of patients; changing recommendations; and general stress [ 5 – 7 ]. However, reductions in Clostridioides difficile have also been reported, [ 1 , 8 , 9 ] and generally a lower rate of multidrug resistant organisms - although this was in an area which was at the time not significantly affected by COVID-19 infections [ 10 ] These have been attributed to the increased awareness and practice of standard precautions [ 1 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that this may be due to: resources shortages; influx of patients; changing recommendations; and general stress [ 5 – 7 ]. However, reductions in Clostridioides difficile have also been reported, [ 1 , 8 , 9 ] and generally a lower rate of multidrug resistant organisms - although this was in an area which was at the time not significantly affected by COVID-19 infections [ 10 ] These have been attributed to the increased awareness and practice of standard precautions [ 1 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 These have been attributed to the increased awareness and practice of standard precautions. 1,10,11 The infection prevention challenges presented by COVID-19 are signi cant. To prepare for the admission and treatment of COVID-19 positive patients, a number of new and modi ed infection prevention initiatives have been implemented across healthcare sites.…”
Section: Introductionmentioning
confidence: 99%